A study on store image attributes and loyalty behaviour - Perumal, Selvan (Universiti Utara Malaysia, 2005)
This study investigates the relationship between store image and store loyalty behaviour for supermarket stores. The study also determines the major attributes in the store image dimentions. The research survey involved a field study using the questionnaire survey method. A total of 204 customers of three supermarkets provided the input for this study. The survey identified five major components of store image attributes, namely,store convenience, conducive atmosphere, value price, employee service and product assortments. The findings of this study revealed a positive relationship between store image attributes and store loyalti behaviour. Analysis of the demographic variables indicated that there is no significant difference among the age groups, genders and income levels for store loyalti behaviour. There are however, some significant differences in store loyalty behaviour among respondents who are married and those with higher education, suggesting that store managers should focus on the needs of these groups.